A németek tájformáló szerepének néhány aspektusa a Bánságban - Mérei, András (Közép-Európai Közlemények, 2010)
Banat was one of the biggest territory of the Folk-Germans in the Carpathian Basin. After re-conquesting the land in 1717, the Habsburger Monarchy established a special administrative unit called „Temesi Bánság”. The Court decided to call roman catholic settlers from Western-Europe to enhance the hegemony of the empire agaist the muslim Ottomans. The settlers were mainly ploughman and handicraft germans from Elsass, Westfalia, Luxemburg, Saxonia, Bavaria, Württemberg), but the land became multiethnical and multireligious because of the Hungarians, Serbs, Romanians and other nationalities (Bulgarians, Jews) by the Germans. One of the most interesting question is how the German nationality and in case –as part of the history –the german Third Reich used and reformed the land „Banat”, what was the agricultural-industrial-cultural effect of the German folk including the Nazi era’s investments. How could the Germans establish new settlerments and build representative districts in the cities. In this study we collect the main flavours of the German attendance (industry, finance, the influence of the Third Reich) which could univocally develop.